The Impact of Modern Politics on Civil Society in Indonesia: A Review of Muhammadiyah's and Nahdlatul Ulama's Political Khittah (State Islamic Institute of Kudus (IAIN Kudus), 2024)
Modern politics, which is of interest to some, has detrimental effects, including on civil society. The main purpose of this research is to determine the impact of modern politics on the subject of research, namely civil society in Indonesia. Through a study of the political khittah of Muhammadiyah and Nahdlatul Ulama, it is corroborated with the theory of civil society from Muhammad Abdul Fattah Santoso and K.H. Asep Saifuddin Chalim. This research uses a literature study method that collects data in the form of books and scientific journals related to the research theme. This research suggests that the impact of modern politics on civil society is quite diverse, ranging from dynastic politics that is authoritarian and disrupts the stability of democracy, the level of trust in leaders in this case the government decreases, to the emergence of an apathetic and pragmatic paradigm towards politics itself. In addition, social media, which is used as a forum for modern politics, contains a lot of hate speech and discredits other groups, which can change the existence of civil society. Muhammadiyah seeks to reconstruct on the basis of the Denpasar Khittah in 2002 coupled with offering a social contract to the government and reflecting on its attitudes and policies towards politics so far. Meanwhile, Nahdlatul Ulama is based on the 1984 NU Khittah which contains the principles of decision-making in political matters, along with reflecting on its attitudes and policies towards politics from time to time.